2022
DOI: 10.1002/ijc.34141
|View full text |Cite
|
Sign up to set email alerts
|

Racial disparities in epithelial ovarian cancer survival: An examination of contributing factors in the Ovarian Cancer in Women of African Ancestry consortium

Abstract: Black women diagnosed with epithelial ovarian cancer have poorer survival compared to white women. Factors that contribute to this disparity, aside from socioeconomic status and guideline‐adherent treatment, have not yet been clearly identified. We examined data from the Ovarian Cancer in Women of African Ancestry (OCWAA) consortium which harmonized data on 1074 Black women and 3263 white women with ovarian cancer from seven US studies. We selected potential mediators and confounders by examining associations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 53 publications
0
14
0
Order By: Relevance
“…57 One such effort studied 10 EOC risk factors and found population risk attributably higher for Black women for all risk factors collectively including family history of breast cancer, body mass index, OCP use, aspirin, and body powder. 58 Other studies found endometriosis and uterine fibroids, but not early menarche, to be relevant risks for Black patients with EOC. 59,60 Enriched data sets such as the Ovarian Cancer in Women of African Ancestry from diverse populations are critical to improve studies of disparities.…”
Section: Disparities In Risk Reduction and Prevention In Ovarian Cancermentioning
confidence: 98%
See 1 more Smart Citation
“…57 One such effort studied 10 EOC risk factors and found population risk attributably higher for Black women for all risk factors collectively including family history of breast cancer, body mass index, OCP use, aspirin, and body powder. 58 Other studies found endometriosis and uterine fibroids, but not early menarche, to be relevant risks for Black patients with EOC. 59,60 Enriched data sets such as the Ovarian Cancer in Women of African Ancestry from diverse populations are critical to improve studies of disparities.…”
Section: Disparities In Risk Reduction and Prevention In Ovarian Cancermentioning
confidence: 98%
“…The Ovarian Cancer in Women of African Ancestry Consortium is a unique harmonized data set of 7 studies with more than 1000 Black women and 3000 White women to better understand risk factors in Black women 57 . One such effort studied 10 EOC risk factors and found population risk attributably higher for Black women for all risk factors collectively including family history of breast cancer, body mass index, OCP use, aspirin, and body powder 58 . Other studies found endometriosis and uterine fibroids, but not early menarche, to be relevant risks for Black patients with EOC 59,60 .…”
Section: Ovarian Cancermentioning
confidence: 99%
“…In an effort to clarify additional factors that contribute to differences in survival rates aside from socioeconomic status and guideline adherent treatment, Harris et al completed a sequential mediation analysis of seven ovarian cancer US studies which found histotype/stage and postmenopausal hormone therapy duration accounted for the largest percentage in disparity [4]. Overall mediators identified including education level, smoking status, nulliparity, BMI, and diabetes explained 48.8% of the overall disparity between Black women and White women in these studies [4]. It is important to note that many of these factors are modifiable allowing for potential targeted interventions to be effective at reducing the gap in survival rates.…”
Section: Difference In Survival Ratesmentioning
confidence: 99%
“…Social determinants of health can also contribute to individual-level susceptibility factors that lead to poorer prognosis, such as higher prevalence of comorbidities and a higher inflammatory response [ 5 , 6 ]. A pooled analysis from the Ovarian Cancer in Women of African Ancestry (OCWAA) consortium suggested that several factors including reproductive factors, comorbid conditions, and hormone use appear to mediate ovarian cancer survival differences between Black and White women [ 7 ].…”
Section: Introductionmentioning
confidence: 99%